Implementasi Mikrokontroler pada Sistem Palang Parkir Otomatis dengan Simulasi Proteus - Raja Syahmuda Siregar (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This research focuses on the design and implementation of an automatic parking barrier system using a microcontroller. The objective is to create an efficient and reliable system that automatically controls the parking barrier in response to vehicle detection. The system utilizes an infrared sensor for vehicle detection, which is processed by a microcontroller to control a servo motor for opening and closing the parking barrier. The research method includes simulation using Proteus software followed by physical implementation. Results show that the system operates efficiently with a quick response time of 1-2 seconds for barrier movement. The conclusion is that the system is effective in automating parking barrier control, reducing human error, and improving parking management. Further improvements can be made by enhancing sensor sensitivity and integrating additional technologies.